2020
DOI: 10.1038/s41589-020-00652-y
|View full text |Cite
|
Sign up to set email alerts
|

PROTAC-mediated degradation reveals a non-catalytic function of AURORA-A kinase

Abstract: Summary The mitotic kinase AURORA-A is essential for cell cycle progression and is considered a priority cancer target. While the catalytic activity of AURORA-A is essential for its mitotic function, recent reports indicate an additional non-catalytic function, which is difficult to target by conventional small molecules. We therefore developed a series of chemical degraders (PROTACs) by connecting a clinical kinase inhibitor of AURORA-A to E3 ligase-binding molecules (e.g. thalidomide). One degrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 57 publications
(51 reference statements)
6
83
0
4
Order By: Relevance
“…Small molecules have been identified that bind to AURKA and alter its conformation in a way that prevents binding to MYCN and result in rapid MYCN degradation (21). More recently, a chemical degrader approach has also been taken (22). While targeting the synthetic lethal interaction between MYCN and the kinase activity of AURKA has to-date failed to provide an efficacious and specific therapeutic, it remains possible that targeting the MYCN stabilizing function of the AURKA-MYCN complex will prove more successful.…”
Section: Mycn As An Attractive Drug Targetmentioning
confidence: 99%
“…Small molecules have been identified that bind to AURKA and alter its conformation in a way that prevents binding to MYCN and result in rapid MYCN degradation (21). More recently, a chemical degrader approach has also been taken (22). While targeting the synthetic lethal interaction between MYCN and the kinase activity of AURKA has to-date failed to provide an efficacious and specific therapeutic, it remains possible that targeting the MYCN stabilizing function of the AURKA-MYCN complex will prove more successful.…”
Section: Mycn As An Attractive Drug Targetmentioning
confidence: 99%
“…Both, 8g and 17b did not induce maximal depletion of WDR5 at high concentrations, a phenomenon called the Hook-effect, resulting from less efficient ternary complex formation at excess degrader levels due to binding site competition (see Figure 3b and 3e). 35 Two negative controls, 20 resembling molecule 8g, and 21 resembling molecule 17b, with the inactive variant of the VHL ligand were synthesised to verify the effect of targeted protein degradation. Their biophysical properties can be found in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Cycloheximide chase assay was performed as described previously. 35 MV4-11 cells were treated with 50 µg/ml CHX with or without PROTACs for different time points. The cells were harvested in RIPA buffer and probed for immunoblotting.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations